2016
DOI: 10.15366/rimcafd2016.63.004
|View full text |Cite
|
Sign up to set email alerts
|

Incorporación de las competencias básicas a la educación física en educación primaria / Integrating Basic Competences into Physical Education (Pe) in Primary Education

Abstract: El objeto de este estudio fue evaluar la percepción de los maestros de Educación Física (EF) del Principado de Asturias sobre el proceso de incorporación de las competencias básicas (CCBB) en el currículo del área. Un total de 151 maestros de EF (46,6% de la población) contestaron a un cuestionario ad hoc compuesto por 12 ítems mediante una escala Likert de 6 puntos. Los resultados mostraron una plena incorporación de las CCBB a las programaciones, sin embargo, el nivel de desarrollo en la práctica resulta ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 9 publications
2
2
1
3
Order By: Relevance
“…In our study, the youngest group of teachers exhibited the most positive perception of the CBCM, which coincides with the findings of other studies such as those by Méndez-Alonso et al (2016) and Lleixá et al (2016). However, our results are in contrast to those of Sharp et al (2011), who found that the most experienced teachers were those who had a most positive perception of the reform.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In our study, the youngest group of teachers exhibited the most positive perception of the CBCM, which coincides with the findings of other studies such as those by Méndez-Alonso et al (2016) and Lleixá et al (2016). However, our results are in contrast to those of Sharp et al (2011), who found that the most experienced teachers were those who had a most positive perception of the reform.…”
Section: Discussionsupporting
confidence: 93%
“…Nonetheless, how to assess competences is one of the greatest obstacles teachers face when putting the CBCM into practice. This is partly consistent with the findings of Méndez-Alonso, Méndez-Giménez, and Fernández-Río (2016), who coincide in that primary school physical education teachers have fully incorporated competences in their planning, but the level of implementation is lower in practical aspects. Mateos Jiménez, García Fernández and Bejarano Franco (2016) and Sharp et al (2011) highlight similar findings in the learning of science competences.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Viendo esta cantidad elevada de propuestas, podríamos afirmar que en España existe unanimidad respecto al cómo podemos implantar de manera rigurosa las CCBB y parece que a nivel formal, en las programaciones, se hace, pero investigaciones recientes han puesto de manifiesto la dificultad de su implantación real en el aula (Méndez-Alonso, Méndez-Giménez y Fernández-Río, 2015, 2016; especialmente por la falta de criterios comunes en su puesta en práctica, ya que cada propuesta lleva consigo una serie de recomendaciones, basadas en unos modelos de actuación que en multitud de casos difieren en gran medida unos de otros (Pérez-Pueyo et al, 2013). Esta complicación se acentúa al tener cada centro total autonomía pedagógica para adecuar sus estructuras organizativas a las características del alumnado, profesorado y contexto.…”
Section: Introductionunclassified